ANALISIS KESALAHAN PENGGUNAAN GYAKUSETSU NO SETSUZOKUJOSHI -PADA MAHASISWA SASTRA JEPANG ANGKATAN 2008 UNIVERSITAS BRAWIJAYA - Sahni, Titah (Jurnal Ilmiah Mahasiswa FIB, 2013)
Conjunctions plays an important role in the delivery of messages through the medium of language. In Japanese there are several kinds of conjunctions, one of which is the continued opposition.  There is a contradiction in conjunction conjunction noni, temo and ga. This study aims to answer the second formulation of the problem, namely (1) whether the type of error made ​​when using gyakusetsu students no setsuzokujoshi (2) whether the cause of the error using gyakusetsu no setsuzokujoshi. This study uses a combination of 2 qualitative and quantitative approaches. The data used as the object of analysis to answer the problem is the result of tests and questionnaires by 33 students of Japanese Literature class of 2008 Univercity of Brawijaya.The results showed that there are 4 types of errors. The type of error is a 71% stacking faults, wrong formations some 22%, the removal of a number of 6%, the addition of a 1%. In addition, also found 4 errors of ignorance will cause restriction rules, one hypothesized concept, excessive generalization and application of the rules is not perfect. Authors suggest further research to analyze more gyakusetsu no setsuzokujoshi like keredomo and shikasi. In addition, to find the cause of the error is not only using a questionnaire but could use the interview as his successor.